Beyond Dichotomies: Subjectivity, Ethics, and Ontology in David J. Gunkel’s Philosophy of Artificial Intelligence - Albano, Norberto; Brignone, Sandro; Urciuoli, Carmine (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2025)
David J. Gunkel is a globally recognized scholar in the philosophy of technology, whose research has profoundly influenced contemporary debates on the ethical and legal status of artificial intelligence and robotics. He currently serves as Presidential Research, Scholarship and Artistry Professor at Northern Illinois University and Associate Professor of Applied Ethics at Łazarski University in Warsaw. His work is distinguished by an interdisciplinary approach that bridges moral philosophy, communication theory, and emerging technologies. Author of numerous publications, Gunkel has significantly contributed to redefining the conceptual foundations of human-machine relations. Among his most recent works are: Communicative AI: A Critical Introduction to Large Language Models (2025, with M. Coeckelbergh), which offers a critical and accessible philosophical and theoretical overview of LLMs; The Rights of Robots (2024), which explores the extension of legal and moral rights to non-human entities; Duty Now and For the Future: Communication, Ethics and Artificial Intelligence (2023), a critical examination of the ethical responsibilities in AI development; and ChatGPT: Deconstructing the Debate and Moving it Forward (2023, with M. Coeckelbergh), which provides a philosophical analysis of conversational AI systems. Through these and many other contributions, Gunkel continues to set the agenda for the ethical interrogation of advanced technologies in a rapidly evolving digital society.